Region-based business strategies: a portuguese case study - Ribeiro, J. Cadima (2008)
Small and Medium size Enterprises (SMEs) located in particular geographical areas are producing and selling regional products to domestic and foreign markets. Most of the local activities are embedded in historical tradition and geographic, cultural and social specificity. This article investigates the effect of local environment on the success of two Portuguese SMEs. We use case study methodology to understand whether local environment influences the nature of the competitive advantage of the small firms and their ability to gain access to resources that enable them to compete with the industrial low price substitutes produced by larger firms. The key conclusion of the study is that the two firms analysed rely strongly on the specific characteristics of the local environment and on partnerships with local producers (raw materials or products) in order to achieve the economic scale that allows them to compete in the domestic and foreign markets.